A Cross Country Study of Indirect Effect of IFRS Adoption on Earnings Management - Agustin Setya Ningrum; Ratna Wardhani; Aria Farah Mita (Journal of Accounting and Investment, 2019)
The main purpose of this study is to investigate whether there is an indirect negative effect of IFRS adoption level on earnings management, through an increase of analyst coverage. This paper is motivated by the fact that IFRS adoption could increase the number of analysts who follow the companies. The existence of analysts will increase the role of oversight of the company, which will decrease earnings management practices. This study is a cross-country study using 3.786 firm years of entities among 30 countries. This study proves that there is indirect positive effect of IFRS adoption level on earnings management, through an increase of analyst coverage. Increase of analyst coverage will push companies to do earnings management practices. This study also confirms that IFRS adoption level has direct negative effect on earnings management. This paper develops new measurement of the IFRS adoption level based on information presented in the IFRS Jurisdiction Profile published by the IFRS Foundation. This measurement is different from previous studies, which generally use dummy variables. More than 100 countries have submitted the IFRS Profile to IFRS Foundation in 2012.  Therefore, we can measure the level of IFRS adoption in many countries. This measurement becomes an additional contribution to further studies.